RUMAH BIBIT SEBAGAI INOVASI DALAM UPAYA MEWUJUDKAN PERTANIAN AREN YANG BERKELANJUTAN - Hazaeri, Ahmad; Martiana, Baiq Elly; Anggriani, Ningsi; Dzuhuriazandi, Muhammad Adjie; Hidayati, Tara Devilia; Widyantara, Ida Bagus Andrew; Savira, Nur; Aini, Jannatul; Masdayanti, Masdayanti; Haris, Ridwan; Budastra, I Ketut (Universitas Mataram, 2023)
Community Service Program (KKN) is a form of community service activities carried out by universities. In the KKN activities carried out in Giri Madia Village, Lingsar District, West Lombok Regency, groups of students and lecturers of Mataram University carried out various activities with the main target of utilizing home yards by making palm seedling houses. The purpose of implementing this KKN activity is to answer the problem of the large amount of vacant land in the yard that is not used and not maintained in Giri Madia village. So the KKN group conducted mentoring activities in the utilization of home yards for making palm seedling houses. There are 6 methods of activities carried out, namely (1) observation, (2) socialization, (3) practice, (4) distribution of plant seeds, (5) monitoring, and (6) evaluation. The results of this activity are expected to increase the knowledge and skills of the Giri Madia Village community regarding the utilization of home yards so that the community can still apply it. The results of the above activities show that this KKN activity has been able to help problems in terms of the utilization of home yards that are not utilized as one of the lands to cultivate quality palm seeds because palm plants that grow wild make people reluctant to cultivate them, it is also expected that the knowledge and skills of the community can increase and the results can help the economy of the Giri Madia Village community.